ILLUSION OF KNOWING IN METACOGNITIVE MONITORING: REVIEW OF POSSIBLE CAUSES AND CONSEQUENCES - Kalamazh, Ruslana; Avhustiuk, Maria (Psychological Prospects Journal, 2018)
The paper highlights possible causes and consequences of the illusion of knowing in metacognitive monitoring of the learning activity of university students through the effects of different types of information proposed, and also of personal, cognitive, metacognitive, and individual psychological characteristics of university students (n = 262; M = 19,5; SD = 1,87). According to the results, the illusion of knowing occurring mostly in prospective judgements of learning can be caused by the type of information (it was higher in the statements), task type (it appeared in multiple-choice questions), text length (its levels were higher in larger texts) and style (overconfidence occurred while learning the texts of the belletristic style). Female students tended towards slight overconfidence and the illusion of knowing was more typical for younger students with lower levels of academic achievements. Possible consequences of the phenomenon, ways of its annihilation, and further avenues for research are also described.